A new species of the Colocasiomyia gigantea species group (Diptera, Drosophilidae) breeding on inflorescences of Scindapsus maclurei (Araceae) - Xue, Xian-Ci; Jiao, Run-Jie; Yu, Li; Gao, Jian-Jun (Zootaxa, 2022)
The gigantea group is one of the six species groups of the genus Colocasiomyia Meijere, 1914 (Diptera, Drosophilidae). All the nine known species of this group breed on inflorescence/infructescence of host plants of the subfamily Monsteroideae (Araceae) and are geographically restricted to the Oriental region: seven species found exclusively from Rhaphidophora spp. in southern China, and the remaining two from Sabah (host plant: Scindapsus coriaceus) in Borneo or from West Java (host plant: Epipremnum pinnatum). In the present paper, a new member of the gigantea group, C. daiae sp. nov., is described, with adult specimens and eggs collected from inflorescences of Scindapsus maclurei in Hainan, China and larvae and pupae reared from field-collected eggs in the laboratory.